Mauritius - Biodiversity Restoration - World Bank (Washington, DC, 2012)
This project (1996-2001), whose total cost was $1.6 million, intended to (a) protect critically endangered biodiversity of international importance by restoring degraded small island habitats and propagating and reintroducing endemic species to these habitats; and (b) strengthen capacity for the management and monitoring of biodiversity restoration.